Application of APACHE II Score in assessing the severity and outcome in peritonitis due to hollow viscus perforation - Reddy, M. Venkat; Reddy, T. Amarsimha; ., Satyadev; Teja, B. RaghuRam; ShanmugaRaju, P. (International Surgery Journal, 2019)
Background: Acute generalized peritonitis from Gastrointestinal hollow viscus perforation is a potentially life threatening condition. The aim of the study was to assess the application of APACHE II score in assessing the severity and outcome in peritonitis due to hollow viscus perforation and to correlate morbidity and mortality patterns using the modified APACHE II Score and its significance on the outcome. Methods: A prospective survey of 50 patients with acute generalized peritonitis due to hollow viscus perforation was carried out in general surgical wards, CAIMS, Karimnagar. APACHE-II scores were assigned to all patients in order to calculate their individual risk of mortality before undergoing emergency surgery. Results: Total 50 patients were admitted during the study period. Age and sex distribution shows that perforation was common >60 years in our study. Higher modified APACHE II scores statistically influenced mortality in all the patients irrespective of aetiology with p<0.001 which is statistically significant. Conclusions: Modified APACHE II scoring predicts mortality which was significant irrespective of the aetiology.